NMR and Bioinformatics Discovery of Exosites That Tune Metalloelastase Specificity for Solubilized Elastin and Collagen Triple Helices - Palmier, Mark O. (American Society for Biochemistry and Molecular Biology, 2010)
The catalytic domain of metalloelastase (matrix metalloproteinase-12 or MMP-12) is unique among MMPs in exerting high proteolytic activity upon fibrils that resist hydrolysis, especially elastin from lungs afflicted with chronic obstructive pulmonary disease or arteries with aneurysms. How does the MMP-12 catalytic domain achieve this specificity? NMR interface mapping suggests that α-elastin species cover the primed subsites, a strip across the β-sheet from β-strand IV to the II–III loop, and a broad bowl from helix A to helix C. The many contacts may account for the comparatively high affinity, as well as embedding of MMP-12 in damaged elastin fibrils in vivo. We developed a strategy called BINDSIght, for bioinformatics and NMR discovery of specificity of interactions, to evaluate MMP-12 specificity without a structure of a complex. BINDSIght integration of the interface mapping with other ambiguous information from sequences guided choice mutations in binding regions nearer the active site. Single substitutions at each of ten locations impair specific activity toward solubilized elastin. Five of them impair release of peptides from intact elastin fibrils. Eight lesions also impair specific activity toward triple helices from collagen IV or V. Eight sites map to the “primed” side in the III–IV, V–B, and S1′ specificity loops. Two map to the “unprimed” side in the IV–V and B–C loops. The ten key residues circumscribe the catalytic cleft, form an exosite, and are distinctive features available for targeting by new diagnostics or therapeutics.